2022
DOI: 10.2147/ppa.s328583
|View full text |Cite
|
Sign up to set email alerts
|

Weight Change and the Association with Adherence and Persistence to Diabetes Therapy: A Narrative Review

Abstract: Purpose Type 2 diabetes (T2D) medication adherence is poor and is impacted by individual drug characteristics. Treatment-associated weight change can affect medication-taking behavior. This review aimed to explore weight change on T2D therapy and consider its impact on adherence and discontinuation. Methods Searches were conducted in MEDLINE and EMBASE (2005 to September 2020), and among recent congress abstract books for studies providing data on medication adherence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Furthermore, our results suggest an association between parallel T2DM risk and body weight gain, which is consistent with previous studies [34,35]. Weight management is essential for better glycemic control [36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our results suggest an association between parallel T2DM risk and body weight gain, which is consistent with previous studies [34,35]. Weight management is essential for better glycemic control [36].…”
Section: Discussionsupporting
confidence: 93%
“…Adherence to the MedDiet was assessed with the MedDiet Score questionnaire, which recorded consumption of the 11 major components (unrefined grains, fruits, vegetables, potatoes, legumes, olive oil, fish, red meat, poultry, full-fat dairy products and alcohol) in a face-to-face interview with a qualified dietitian. The MedDiet score is categorized as no adherence (0-13), inadequate adherence (14-27), satisfactory adherence (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and very good adherence (42-55) [19].…”
Section: Adherence To Meddietmentioning
confidence: 99%
“… 31 Patients with both conditions are likely to adhere to GLP-1 RA therapy better than diabetes patients without obesity, 32 and patients with diabetes mellitus who achieved substantial weight loss had significantly better adherence to medication and other treatment regimens than those with weight gain. 33 , 34 Therefore, it is not surprising that patients with both obesity and diabetes who achieved weight loss in our study displayed better than average adherence. For such patients, treatment using GLP-1 RAs such as liraglutide 3.0 mg are a viable option for achieving both weight loss and glycemic control.…”
Section: Discussionmentioning
confidence: 62%
“…Changes in BMI are likely to be informative of potential changes in apnea-hypopnea index, as decrease in BMI may be associated with decreased apnea-hypopnea index, that could affect adherence to the treatment. Moreover, previous studies suggested that BMI changes could affect adherence to therapies and a potential relationship between CPAP use and BMI changes has been reported . BMI has therefore been proposed to be a driver of CPAP adherence.…”
Section: Discussionmentioning
confidence: 99%